The Influence Of Psychoeducation On Knowledge And Attitudes On The Importance Of Asi As A Stunting Prevention Measure Among Caders In Rasau Jaya - Pratika Sari; Riszky Ramadhan; Selviana, Selviana (Jurnal EduHealth, 2024)
Stunting is a serious problem experienced by Indonesian children due to prolonged malnutrition. ASI (breast milk) has a significant role in preventing stunting. This research aims to find out whether there is an influence of psychoeducation on knowledge and attitudes about the importance of breastfeeding as an effort to prevent stunting in cadres. The approach used in this research is quantitative with experimental research methods. The type of experiment used is Pre-Experimental Design with the design approach "One Group Pre-test Post-test. Based on the results of the Wilcoxon Signed Rank Test calculation, the Z value obtained is -3.192 with a p-value (Asymp. Sig 2 tailed) of 0.001 which is less than the research critical limit of 0.05 so the hypothesis decision is to accept the alternative hypothesis (H1) or which means there is a significant difference between the pre-test and post-test groups.